Escritura, ficción, imagen. Transformaciones del lazo cine- literatura argentinos - Marcos Zangrandi (Cuadernos LIRICO)
This article studies the literature-cinema relationship in Argentina in three historical scenarios: the major film studios scheme, the modernization and diversification of the screen in the 1950s and 1960s, and the passage from the 20th to the 21st century. In this line, the bond between the two spaces was affirmed and transformed. Faced with the parceling model of the industrial period, collaborations between filmmakers and writers emerged, and with them, affinities and reciprocal interests. The recent production of Martín Rejtman and Mariano Llinás points to a new inflection that accounts for a shift from film writing to the problematization of fiction.